The effect of the most abundant bioactive compounds of the mediterranean diet on the osteoblast-mediated osteoclast differentiation signaling pathway: in silico analysis - Markovic, Nemanja; Mijuskovic, Svetozar; Jovanovic, Mirjana; Mitovic, Nikola; Nenadovic, Aleksandra; Vukovic, Andrija; Kovacevic, Sanjin; Kosic, Marija; Juloski, Jovan; S. Stankovic, Marija; Nesovic Ostojic, Jelena (Medical Research, 2025)
Introduction: Bones are fundamental components of the skeletal system that continuously remodel throughout life. Osteoclasts are responsible for bone resorption, while osteoblasts form new bone matrix and indirectly influence osteoclast differentiation through signaling pathways involving molecules such as M-CSF, c-Fms, GRB2, ERK, PI3K, and Akt. To maintain bone health, increasing attention is being given to nutritional interventions, including the Mediterranean diet, which is rich in bioactive compounds. The aim of this study was to perform an in silico analysis of potential interactions between the most prevalent bioactive compounds of the Mediterranean diet and the key proteins of the osteoclast differentiation signaling pathway.Materials and Methods: A library comprising 115 predominant bioactive compounds from the Mediterranean diet was constructed based on literature data. Protein structures obtained via crystallography were used as targets in molecular docking simulations to predict interactions between ligands and receptors.Results: Most ligands did not show significant interactions with the investigated proteins (ΔG > −7 kcal/mol), except in the case of Akt protein. For this protein, a larger number of ligands demonstrated ΔG values < −7 kcal/mol. The five most potent ligands (salvianolic acid, apigenin, diosmin, mangiferin and sylbin) bound to amino acid sequences forming the active site of the receptor, indicating a potential inhibitory effect.Conclusion: The in silico analysis suggests that bioactive components of the Mediterranean diet possess potential to inhibit Akt protein (protein kinase B), thereby opening new perspectives for their application in modulating osteoclast activity and developing novel strategies for maintaining bone health.
Keywords: Mediterranean diet; Bioactive compounds; Osteoblasts; Osteoclasts; Protein kinase B